THE EFFECT OF MATHEMATICS PROBLEM-SOLVING ABILITY AND LEARNING INDEPENDENCE ON MATHEMATICS LEARNING ACHIEVEMENT IN ONLINE LEARNING - Joko Purwanto; Isytifa Noor Rahma; Gunawan Gunawan; Jaka Wijaya Kusuma (Yayasan Education and Social Center, 2022)
The COVID-19 pandemic has made face-to-face learning abolished and substituted by online learners, causing the value of mathematical learning performance to fall. It is possible that mathematical problem-solving skills and learning independence are variables that a ffect the reduction in learning achievement in mathematics. This study aimed to examine the effect of partial and simultaneous mathematical problem-solving ability and independent learning on mathematics learning achievement. This study was carried out at SMP N 1 Purwokerto, with the population was class IX SMP N 1 Purwokerto, the sample selected by cluster random sampling was class IX H SMP N 1 Purwokerto. A quantitative study using the ex-post-facto method was used in this study. Tests, surveys, and score documents were used to collect data. Validity and reliability assessments were completed on the tests and surveys. A precondition test, such as a normality test, multicollinearity test, heteroscedasticity test, and linearity test, was performed on the questionnaire test results. After that, a multiple linear regression model and test the hypothesis were formed using coefficients of determination, partial test, and simultaneous test methods. Y=49,280+0,107X1+0,378X2 was the linear regression model formed. According to the findings, mathematical problem-solving skills showed a significant effect on the learning achievement of 10.7%. Learning autonomy had a 37.8% positive effect on learning achievement. Simultaneously, the ability to solve mathematical problems and autonomous learning had a 70.7% significant effect on learning achievement